Diversity in Phase 2 and Phase 3 Placebo‐Controlled, Double‐Blind, Lecanemab and Elenbecestat Early Alzheimer's Disease Studies. (20th December 2022) - Grill, Joshua; Molina‐Henry, Doris P.; Sperling, Reisa A.; Dhadda, Shobha; Tranotti, Kate; Harris, Russell; Devins, Theresa; Swanson, Chad J; Kanekiyo, Michio; Gee, Michelle; Irizarry, Michael C; Kramer, Lynn D; et al.
Abstract: Background: Increasing diversity in clinical trials is a scientific, public health, and ethical imperative. Clinicians need to understand how a drug works in representative disease populations, diverse communities need access to clinical trials, and social justice demands addressing health and healthcare disparities. Several factors contribute to underrepresentation among racial and ethnic groups in Alzheimer's disease (AD) clinical trials, including barriers to enrollment but also potential differential exclusion based on eligibility criteria. Method: We evaluated enrollment in four double blind placebo‐controlled clinical trials in early AD that incorporated highly similar enrollment criteria (NCT03887455, NCT01767311, NCT02956486, NCT03036280). We assessed the impact of eligibility criteria. Racial and ethnic information were self‐reported by participants and are reported as mutually exclusive categories. Each trial incorporated PET or CSF to evaluate brain amyloid pathology, as well as typical inclusion and exclusion criteria used in early AD trials. Result: Across the trials, 10, 805 US participants were screened: 889 (8%) were of Black race, 119 (<1%) were of Asian race, and 2, 883 (27%) were of Hispanic ethnicity. 2, 459 participants were randomized, including 97 (4%) of Black race, 17 (<1%) of Asian race, and 450 (18%) of Hispanic ethnicity. Overall, 23% of those screened were randomized: 27% of non‐Hispanic White participants compared to 11% of Black race participants, 14% of Asian race participants, and 16% of Hispanic ethnicity participants. The distribution of age and disease stage (MCI or mild AD) among screened and randomized participants were similar across the racial and ethnic groups. Females appeared to be more highly represented among Black race and Hispanic ethnicity participants, compared to non‐Hispanic White participants. Five inclusion and exclusion criteria, including AD biomarker criteria, resulted in greater than 60% of screen failures across the trials, with some variability in specific eligibility criteria across racial and ethnic groups. Conclusion: Early AD clinical trials have high rates of screen failure and exploration of potential differential screen failure among racial and ethnic groups will be important to future trial design choices.